PAJAK SORE: RE-DESIGN OF PADANG BULAN TRADITIONAL MARKET WITH THE URBAN ACUPUNCTURE CONCEPT - Manik, Baga Rezky Albert; Sembiring, Sri Gunana (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Traditional markets are an important part of urban life in Indonesia. Traditional markets are still often found in Indonesia, especially in residential areas. However, rapid urbanization and the development of modern markets have placed traditional markets under significant pressure. This research aims to explore how the concept of urban acupuncture can be applied as a revitalization step to strengthen the role of traditional markets in the balance of urban ecosystems. Padang Bulan Market, a traditional market in Padang Bulan Village, Medan, faces challenges in maintaining its relevance amidst the city's rapid development. The market faces various challenges, including aging infrastructure and a lack of visitor attractions. Based on existing findings, a redesign plan was developed, taking into account the principles of urban acupuncture. Urban acupuncture is an urban design approach that aims to heal urban disorders through intervention at specific disturbed points. These plans include infrastructure updates, facility improvements, and more functional space arrangements. In addition, the plan also proposes the integration of cultural and community elements that enrich the visitor experience. In facing the challenges of urbanization, this approach emphasizes the important role of traditional markets in promoting economic and social sustainability in a growing urban context.